Electrochemical and in situ X-ray spectroscopic studies of MnO2/reduced graphene oxide nanocomposites as a supercapacitor. Issue 28 (28th April 2016) - Chang, Han-Wei; Lu, Ying-Rui; Chen, Jeng-Lung; Chen, Chi-Liang; Lee, Jyh-Fu; Chen, Jin-Ming; Tsai, Yu-Chen; Yeh, Ping-Hung; Chou, Wu Ching; Dong, Chung-Li
Abstract : An in situ XAS investigation reveals charge–discharge mechanisms of MnO2 /carbon-based materials. Abstract : Electrochemical and in situ X-ray absorption spectroscopy (XAS) measurements of various MnO2 -coated carbon materials (MnO2 /acid-functionalized carbon nanotubes (C-CNT), MnO2 /reduced graphene oxide (RGO), and MnO2 /RGO-Au electrodes) were conducted to evaluate the supercapacitive performances and electronic structures. MnO2 was deposited on the surface of C-CNT, RGO, and RGO-Au via a spontaneous redox reaction to facilitate the growth of the bulk form of MnO2 /C-CNT and the surface forms of MnO2 /RGO-based materials. Various forms of MnO2 on the carbon materials exhibited different charge/discharge behaviors. The specific capacitances of the MnO2 /RGO and MnO2 /RGO-Au electrodes at a current density of 1 A g −1 were about 433 and 469 F g −1, respectively; these values are about 1.5 times that of the MnO2 /C-CNT (259 F g −1 ) electrode. Specific capacitances of 220 and 281 F g −1 with retention rates of about 50–60% were obtained from MnO2 /RGO and MnO2 /RGO-Au, respectively, even at a high current density of 80 A g −1 . Experimental results revealed that the long-term electrochemical stability of the MnO2 /RGO-based electrodes (with ∼90% retention) exceeded that of the MnO2 /C-CNT electrode (with ∼60% retention) after 1000 cycles at a high scan rate of 80 A g −1 . This finding indicates that MnO2 /RGO-based electrodes feature excellent cycling stability and rate capacity retention performance. To elucidate the atomic/electronic structures of the MnO2 /C-CNT, MnO2 /RGO, and MnO2 /RGO-Au electrodes during the charge/discharge process, in situ XAS of the Mn K-edge was performed. The MnO2 /RGO-based electrodes exhibited the least variations in the pre-peak intensity of the Mn K-edge during the charge/discharge process because a nano-network of MnO2 is homogeneously decorated on the outer surfaces of RGO-based electrodes to facilitate the growth of surface forms of MnO2 /RGO and MnO2 /RGO-Au. Analytical results further revealed suppression of changes in tunnel size and promotion of insertion/extraction behavior. This work, particularly the combination of cyclic voltammetry with in situ XAS measurements, will be of general value in the fields of nanomaterials and nanotechnology, and in their use in energy storage.